Justice in Lyon: Klaus Barbie and France's first trial for crimes against humanity - Golsan, Richard Joseph (University of Toronto Press, 2022)
The trial of former SS lieutenant and Gestapo chief Klaus Barbie was France’s first trial for crimes against humanity. Known as the "Butcher of Lyon" during the Nazi occupation of that city from 1942 to 1944, Barbie tortured, deported, and murdered thousands of Jews and Resistance fighters. Following a lengthy investigation and the overcoming of numerous legal and other obstacles, the trial began in 1987 and attracted global attention.